Epibenthic macrofauna on an artificial reef of the Northern Adriatic Sea - Bettoso, Nicola (Annales. Series historia naturalis, 2023)
Artificial reefs (ARs) are man-made structures used with the aim of improving fisheries and increasing natural production of biological resources. In 2006 an AR made of three types of modules was sunk near an underwater sewage outfall. The objectives of the project were: (a) to use the AR to restock some target species of commercial interest and (b) to promote biodiversity in selected areas. The epibenthic macrofauna that had settled on this AR was annually monitored for five years (2007-2011) using non-destructive photographic methods. A total of 88 taxa from 8 phyla were identified, with a predominance of Porifera, Mollusca and Ascidiacea. Among the types of modules used to construct the AR, polyethylene panel nets were functional for bivalve settlement in the first year, whereas concrete structures seemed to perform best in promoting biodiversity in terms of species richness in the long term. Nevertheless, the 5-year monitoring period was too short to speculate on the stability or homeostasis of communities settled on the AR in terms of ecological succession.
Keywords: Adriatic Sea; artificial reefs; barriere artificiali; biologia marina; fotografski monitoring; hidrobiologija; hydrobiology; idrobiologia; Jadransko morje; macrozoobenthos; makrozoobentos; mare Adriatico; marine biology; monitoraggio fotografico; morska biologija; photographic monitoring; umetni podvodni grebeni